Monetary Transmission Mechanisms In Five ASEAN Countries - Yusof, Zarinah (2006)

(untitled)
This study examines monetary transmission mechanisms in ASEAN countries, namely Malaysia, Indonesia, the Philippines, Singapore and Thailand, for the period 1970:1- 2002:4. Views diverge among economists on how monetary policy variable affects the economic activity. The traditional theory explains that money is more important. Via interest rate, money affects the economy. However, it has been challenged by some economists who believe that bank credit has a major role. In addition, in a highly internationalized economy and mobility of capital is rapid, changes in exchange rate have major impact on output and prices but the effects have always been left out. Using analysis of cointegration and vector error correction model (VECM), the study estimates both aggregate and sectoral output to examine the channels. The findings resolve the dispute. Money, bank credit, interest rate and exchange rate significantly affect economic activity and active channels. Further evidence finds that highly liquid money (M1) is more influential in Malaysia and the Philippines. Broad money (M2) is more superior in Indonesia and Thailand. Singapore’s well-developed financial market exhibits the importance of bank lending channel. Exchange rate is important particularly in Singapore and Malaysia’s manufacturing sector. The Asian financial crisis in mid-1997 had significant impact on Malaysia and Thailand. Indonesia is more affected by the early 1980s financial reforms. Oil price shock in 1979-1981 has significant impact on the economy of Thailand. Only estimates on Malaysian sectoral output gave satisfactory results and were discussed. The findings found strong evidence that all the channels are important. The evidence highlights highly liquid money (M1) has stronger effects on the output of agricultural and manufacturing sectors. Broad money (M2) has greater impact on services output and credit is the main transmission mechanism in construction output. Notable finding is rapid modern sophisticated technological banking facilities have resulted in a fundamental change in the behavior of M1. All the channels are crucial and it is money that matters most.